The National Treatment Purchase Fund ? A success for some patients yet a public policy failure? - Burke, Sara; Thomas, Stephen (My University, 2019)
In 2002 the Irish Government announced the establishment of the National Treatment Purchase Fund (NTPF) as a means of addressing patients’ long wait times for public hospital treatment. A new health strategy published in December 2001 promised that ‘by the end of 2004 all public patients will be scheduled to commence treatment within a maximum of three months of referral from an outpatient department’. Qualitative methods, including documentary analysis and key informant interviews, were used to gain an understanding of this policy process. The findings were then analysed through the framework proposed for this special issue where ideas, institutions and politics interact. Using McConnell’s typology of policy failure, this research finds the NTPF to be an example of a policy failure because, even though tens of thousands of public patients were treated under the NTPF, waiting times and numbers have persisted and escalated since the NTPF was established.
PUBLISHED
DOI: https://doi.org/10.2478/admin-2019-0013
Keywords: Health policy analysis; Irish health reform; Privatisation; Hospital care; Policy failure; Inclusive Society; Making Ireland; Health policy; Health policy analysis; Health system reform; Health systems research; Irish health system; Political Science; health systems and policy; Health; Policy